Reduced-Calorie Apricot-Based Lacto-Fermented Beverages: Evaluation of Probiotic Content, Physicochemical, and Sensory Properties - Akman, Perihan Kubra; Ozkaya, Gulsum Ucak; Duskun, Beyzanur; Kutlu, Gozde; Tornuk, Fatih; Durak, Muhammed Zeki; Yetim, Hasan (WILEY, 2025)
Optimizing the formulation is essential to enhance probiotic viability, sensory quality, and shelf-life stability, thereby supporting the development of a consumer-acceptable and commercially viable non-dairy functional beverage. This study focused on optimizing the fermentation process of apricot-based beverages using three probiotic strains: Lactiplantibacillus plantarum XL963 (LP), Limosilactobacillus fermentum W8 (LF), and Lactiplantibacillus pentosus ML104 (LPN). Fermentation conditions were optimized by varying sugar content (9-15%) and fermentation temperatures (20 degrees C, 28.5 degrees C, and 37 degrees C) to maximize sensory properties, lactic acid bacteria (LAB) counts, and probiotic viability over 60 days of storage. Following fermentation optimization, beverages with a calorie reduction exceeding 30% were identified, and their physicochemical properties were evaluated throughout the refrigerated storage period for 60 days. LAB counts increased up to 5-6 log units (11.39 +/- 0.85-14.69 +/- 0.40 colony-forming units (CFU)/mL) during fermentation, rising from initial levels (9.04 +/- 0.36-9.08 +/- 0.84 log CFU/mL). Throughout the 10-day storage period, viable LAB populations were maintained above the critical threshold of 10(6) CFU/mL, with counts ranging from 9.13 +/- 0.05 to 13.80 +/- 0.06 log CFU/mL during storage, as determined by the spread plate method. Calorie reductions ranged from 24.48% to 59.49%, depending on fermentation temperature, sugar content, and the probiotic strain used. The overall sensory acceptability scores of the LF, LP, and LPN samples-fermented under varying sugar concentrations (9-15%) and fermentation temperatures (20 degrees C, 28.5 degrees C, and 37 degrees C)-ranged between 3.34 and 7.60, based on the average values obtained immediately after fermentation and following 10 days of refrigerated storage. Significant changes (p < 0.05) were observed in physicochemical properties, with soluble solids content between 20.73 +/- 0.17 and 23.87 +/- 0.06, pH values from 3.88 +/- 0.01 to 4.28 +/- 0.01, and dry matter content between 22.45 +/- 0.02% and 26.01 +/- 0.37%. Turbidity values ranged from 0.057 +/- 0.002 to 0.176 +/- 0.0012, while L*, a*, and b* values ranged from 28.45 +/- 0.08 to 34.12 +/- 0.56, 1.06 +/- 0.04 to 3.43 +/- 0.16, and 11.36 +/- 0.16 to 18.47 +/- 0.24, respectively. The color difference (Delta E*) ranged from 0.22 to 16.98, with the highest values observed at the beginning of storage. During the 60-day storage period, apricot beverages containing 12% added sugar and fermented with LF, LP, LPN, and the mix culture (LF + LP + LPN) maintained favorable sensory scores, with values ranging between 6.27 +/- 0.82 and 7.18 +/- 1.17 for taste, 5.85 +/- 0.80 and 7.09 +/- 0.60 for color and appearance, 5.82 +/- 0.80 and 7.00 +/- 0.77 for texture, 6.00 +/- 0.83 and 7.00 +/- 0.70 for smell, and 6.00 +/- 0.65 and 7.00 +/- 1.00 for overall acceptability. In conclusion, this study successfully developed reduced-calorie, probiotic-rich, and sensorially acceptable apricot-based beverages, providing a promising functional drink for consumers.
Keywords: apricot-based drink; lacto-fermented; non-dairy probiotic beverage; physicochemical properties; reduced calorie; JUICE; Food Science & Technology